Seasonality of fecal androgen and glucocorticoid metabolite excretion in male goral (Naemorhedus griseus) in Thailand - Jaruwan Khonmee (2018)
There is no information on the endocrinology of Chinese goral (Naemorhedus griseus), a high priority species for captive breeding and reintroduction in Thailand. This study characterized fecal androgen and glucocorticoid metabolites in male goral at Omkoi Wildlife Sanctuary to investigate seasonal relationships. Fecal samples were collected 3 days/week for 1 year from eight adult males. Mean androgen metabolite concentrations were greater (P < 0.05) during the rainy season (289.82. ±. 9.18. ng/g) and winter (224.09. ±. 11.97. ng/g) compared to the summer (195.48. ±. 8.23. ng/g), and were related to breeding activity. A similar pattern was observed for glucocorticoid concentrations (22.10. ±. 0.72. ng/g compared to 21.98. ±. 0.98. ng/g compared to 15.30. ±. 0.48. ng/g), respectively, and this resulted in a positive correlation between the two hormones (P < 0.05). There also were positive correlations between fecal androgen metabolite concentrations and temperature (P < 0.05) and day length (P < 0.05). In summary, this is the first study to assess endocrine function in male goral, and results showed seasonal variation in testicular and adrenal steroidogenic function, with greater activity in the rainy season and winter. Given that resources for captive male goral are consistent throughout the year, reproduction may be regulated primarily by photoperiod in this species. © 2014 Elsevier B.V.